FECUNDITY OF CARP MINNOW SALMOSTOMA BACAILA (HAM.) - Piska, Ravi Shankar; Waghray, Sarala (Indian Journal of Fisheries, 2011)
The fecundity in Salmostoma bacaila (Ham.) was found to range from 9,873 to 29,960 in fishes of total lengthrange 97 to 140mm. The Log fecundity has straight line relationship with Log total length, Log bodyweight, Log length and Log weight of ovaries. Cube relationship is found between total length andfecundity.